Pengaruh Kompetensi dan Kompensasi Terhadap Kinerja Karyawan Airport Security PT. Angkasa Pura I Bandara Internasional Juanda Surabaya - Putri Sariva Hamiidah Yulintyani; Setya Prihatiningtyas; Chasan Azari (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2024)
Study aims to determine the effect of competence and compensation on the performance of Airport Security employees of PT. Angkasa Pura I Juanda International Airport Surabaya using quantitative methods with a casual relationship approach. The sampling technique used is Stratified Random Sampling. The total population is 111 employees with a sample of 53 employees of the Airport Security section of PT. Angkasa Pura I Juanda International Airport Surabaya. The results of this study proved that the partial test (t-test) of the Competency variable (X1) obtained a significant value of 0.000 < 0.05 and tcount 3,824 > table 2,009 which had a significant effect, while the partial test (t-test) of the Compensation variable (X2) obtained a significant value of 0.000 < 0.05 and the tcount test of 7,942 > table 2,009 which had a significant effect. Simultaneously (Test F) by obtaining significant values of 0.000 > alpha 0.05 and Fcalculate 108. 844 > a value of Ftable 3.18 means that it has a significant effect on employee performance. The importance of attention to employee competency development and compensation system improvement as a strategy to improve performance in the Airport Security sector of PT. Angkasa Pura I Juanda International Airport Surabaya. This research is expected to provide guidance for PT Angkasa Pura in designing more effective human resource policies, focusing on developing employee competencies and improving the compensation system.